The Republic of Lithuania : Second Review Under the Stand-By Arrangement-Staff Report; News Brief on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Lithuania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper evaluates the Republic of Lithuania's Second Review Under the Stand-By Arrangement. Program implementation has been generally good. Macroeconomic performance was better than expected in 2001: real GDP grew by 5.9 percent, driven by buoyant exports and investment, while the impact of the slowdown in the European Union was limited and largely offset by strong demand from Commonwealth of Independent States (CIS) countries. The macroeconomic outlook for 2002 envisages faster growth and a slightly higher current account deficit, while inflation, wage, and employment projections remain largely unchanged.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet